FROM FRAGMENTATION TO WHOLENESS: THE ROLE OF DECONSTRUCTION IN THE REPRESENTATION OF THE MIAO IN CONTEMPORARY PAINTING - Zhenchao Li; Tetrina Ahmed Fauzi (Fonseca, Journal of Communication, 2025)
Using modern art, a great tool for communication, one may challenge preconceptions and disjointed images of the Miao ethnic group. Modern artists apply deconstruction to turn painting into a dynamic medium for creative debate. This approach uses audience involvement, abstraction of established cultural ciphers, and historical and modern elements. Using the eradication of archaic concepts, this method not only acts as a means of criticism aimed at society but also promotes a natural respect for Miao culture. This project aims to investigate how painting could help promote fairness and diversity in portraying cultural traditions. The study is based on deconstruction and postcolonial philosophy, which guides ideas for the investigation. Based on the research results, this study implies that by applying the strategies presented here, politicians, teachers, and artists could foster cultural understanding via the art media. The research data supports this claim.